The Role of Consumers’ Behaviour in Applying Green Marketing: An Economic Analysis of the Non-alcoholic Beverages Industry in Kosova - Podvorica, Ganimete; Ukaj, Fatos (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
Green marketing in Kosova evolved as a means for enterprises to adjust to increased market competitiveness. The objective of the study was to identify how consumers’ environmentally friendly behavior drove the demand for new eco-value market offerings. Concurrently, the study aimed to prove how domestic producers of nonalcoholic beverages used their capabilities to deliver new eco-value market offerings. The research is based on a survey conducted in Kosova. Analysis focused on statistical correlation testing of consumers’ green marketing awareness, behavior toward the environment, information search, trust in advertising and labels displaying health benefits of beverages, and attitudes towards a willingness to pay more for organic nonalcoholic beverages compared to non-organic ones. Significant findings were the positive influence of family and media in shaping consumers’ environmentally friendly behavior and, in contrast, consumers’ mistrust in the marketing activities of producers as a consequence of misleading advertising.
Keywords: przyjazne dla środowiska zachowania konsumentów; zielony marketing